2022
DOI: 10.1002/ijc.34172
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA‐seq dissecting heterogeneity of tumor cells and comprehensive dynamics in tumor microenvironment during lymph nodes metastasis in gastric cancer

Abstract: Lymph node metastasis is the common metastasis route of gastric cancer. However, until now, heterogeneities of tumor cells and tumor microenvironment in primary tumors (PT) and metastatic lymph nodes (MLN) of gastric cancer (GC) remains uncharacterized. In our study, single cell RNA sequencing was performed on tissues from PT and MLN of gastric cancer. Trajectory analysis and function enrichment analyses were conducted to decode the underlying mechanisms contributing to LN metastasis of gastric cancer. Heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Our results showed that angiogenesis-related gene sets were significantly upregulated in Cd4 + , and Cd8 + T-cells and Tregs. Consistent with our findings, a recent study demonstrated an increase in the proportion of T cells, B cells, DCs and natural killer (NK) cells in metastatic lymph nodes [ 67 ]. Interestingly, the accumulation of N2 type neutrophil (Cd54 low ) was significantly enhanced.…”
Section: Metastatic Spread Via Blood and Lymphatic Vesselssupporting
confidence: 92%
“…Our results showed that angiogenesis-related gene sets were significantly upregulated in Cd4 + , and Cd8 + T-cells and Tregs. Consistent with our findings, a recent study demonstrated an increase in the proportion of T cells, B cells, DCs and natural killer (NK) cells in metastatic lymph nodes [ 67 ]. Interestingly, the accumulation of N2 type neutrophil (Cd54 low ) was significantly enhanced.…”
Section: Metastatic Spread Via Blood and Lymphatic Vesselssupporting
confidence: 92%
“…61 Qian et al revealed the heterogeneities of the TME in primary tumours and metastatic LNs of gastric cancer. 62 Liu et al generated single-cell maps of PT and paired LN met in eight patients with breast cancer and reported that B and CD4 T cells were enriched in the microenvironment of LN met ; however, CD8 T cells, cancer-associated fibroblasts and mast cells were abundant in PT. 63 TME heterogeneity between the primary tumour and locoregional metastases in the same patient may account for differences in response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Through single‐cell RNA sequencing, researchers from another team mapped the lymph node metastasis landscape of GC and found that lipocalin 2 (LCN2) + neutrophils served as a promotor in lymph node metastasis. This suggested that neutrophil subsets might drive metastatic in specific tumor sites 291 . The number of PD‐L1 + neutrophils and CD66b + neutrophils are associated with the survival of GC patients 292–294 .…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%
“…Targeting tumor‐associated CXCR2 + neutrophils and CCR2 + macrophages was reported to improve chemotherapeutic responses in pancreatic ductal adenocarcinoma 342 . In a nutshell, a series of studies have shown that it is necessary to investigate neutrophil heterogeneity in the context of pancreatic cancer treatment 266–343 . For subsequent investigation, the inductive factors of the emergence of diverse neutrophil subsets may be probed, enabling a brand‐new viewpoint for the treatment of pancreatic cancer.…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%